Predictive value of endoscopic findings in the diagnosis of active intestinal amebiasis - Nagata, N.; Shimbo, T.; Akiyama, J.; Nakashima, R.; Niikura, R.; Nishimura, S.; Yada, T.; Watanabe, K.; Oka, S.; Uemura, N. (Endoscopy, 2012)
Endoscopic diagnosis of amebic colitis can be difficult because its appearance may mimic other forms of colonic disease. The aim of this study was to identify predictive endoscopic findings for amebic colitis. Patients with suspected amebic colitis based on distinctive endoscopic findings such as aphthae or erosions, ulcers, exudates, or a bump, were included in the study. A total of 157 patients were selected, 50 of whom had amebic colitis. The sensitivity and specificity of endoscopic findings that were significantly associated with amebic colitis were: cecal lesions (80 % and 54 %), multiple number of lesions (96 % and 29 %), presence of aphthae or erosions (84 % and 37 %), and presence of exudate (88 % and 74 %). Multivariate analysis revealed that the best combination of findings to predict amebic colitis was the presence of cecal lesions, multiple lesions, and exudates, which corresponded to an area under the receiver operating characteristic curve of 0.89 (95 % confidence interval 0.82 – 0.95).